A quantitative study of the effect of the translator’s cultural identity on the Chinese-English translation of Singaporean cultural references - Bai, Kelei (2019)
According to Gideon Toury, in order to become a translator within a cultural environment, an individual has to first acquire a set of norms to determine the suitability of his/her translation and to manoeuvre between all the factors that may restrict the translation process. The aim of this study is to investigate whether a translator’s cultural identity affects his/her performance in the Chinese-English translation of the cultural references in Singaporean literature. Two books written by renowned Singaporean Chinese author, You Jin, were chosen because they contain a number of Singaporean cultural references. The two books were translated by two different translators: one with a prominent Singaporean cultural identity and the other without. For each source text, the cultural references were identified, and the translation of each was then assessed for both accuracy and acceptability. The proportion of cultural-reference translation errors made for each translated text was then calculated. Hypothesis-testing at the 5% level of significance was then carried out on the proportion of errors to determine whether there is any statistical difference between the performance of both translators. The outcome of the hypothesis-testing indicated that even though there is no significant difference between the performance of both translators, the proportion of mistakes made was considerable. Further analysis of the errors showed they were mainly linked to education and food in Singapore for the possible reasons of generation gaps and a rich diversity of cuisine, and a lack of firsthand experience with the local education system.